Etiology of severe acute respiratory infections among adults in northern Thailand using multiplex PCR: A post-COVID-19 surveillance study (2023–2024) - Nang Kham-Kjing; Rathakarn Kawila; Patcharaporn Tariyo; Kittiyaporn Puapun; Sirinat Wongchotbrorirak; Nicole Ngo-Giang-Huong; Sayamon Hongjaisee; Woottichai Khamduang (PLoS ONE, 2026)
Introduction The COVID-19 pandemic disrupted the circulation patterns of respiratory viruses. In tropical regions like Thailand, ongoing surveillance is essential to understand the etiology of severe acute respiratory infections (SARIs) in the post-pandemic era. We investigated the etiology of SARI among hospitalized adults in the post-pandemic era. Methods We conducted a retrospective analysis of respiratory samples collected from adult patients (≥18 years) who were hospitalized at a regional hospital in Chiang Mai, Thailand, between November 2023 and April 2024 due to symptoms of SARI (fever of ≥38°C, cough, and onset within 10 days). Sputum and/or nasopharyngeal swab were collected at admission and tested using a multiplex real-time PCR assay targeting 22 respiratory viruses and Mycoplasma pneumoniae (Siemens Healthineers Fast Track Diagnostics and Tellgen SARS-CoV-2 Nucleic Acid Detection Kit). Demographic, clinical, treatment, and comorbidity data were extracted from hospital records, and descriptive statistics were used to summarize patient characteristics and pathogen distribution. Results Among 101 hospitalized SARI patients (median age 62 years (interquartile range 43–71); 57 males), 47 (47%) tested positive for at least one respiratory pathogen. The most frequently detected viruses were adenovirus (17/101, 17%) and rhinovirus (13/101, 13%). Co-infections occurred in 9% (9/101) of cases. Seasonal trends showed peaks of influenza A and rhinovirus in January, while adenovirus and enterovirus circulated consistently throughout the study period. Conclusions Nearly half of adult SARI cases were associated with viral pathogens. Other SARI etiologies could be due to bacterial or fungal infections not tested in our study. The high rate of empiric antibiotic use highlights the need for broader and rapid molecular diagnostics. Enhanced pathogen-specific surveillance is essential to guide evidence-based clinical management in the post-pandemic context.